2018
DOI: 10.5935/1984-0063.20180044
|View full text |Cite
|
Sign up to set email alerts
|

A nonparametric methodological analysis of rest-activity rhythm in type 2 diabetes

Abstract: The purpose of this study was to analyze the rest-activity rhythm of type 2 diabetics mellitus (T2DM) and compare it to healthy controls using the nonparametric analytic approach. Twenty-one diabetics and 21 healthy subjects matched for gender and age were recruited to participate in the study. Data were analyzed using the Independent t-test, Mann-Whitney U test, and Spearmans correlation. T2DM subjects demonstrate lower interdaily stability (IS) (p=.03), higher intradaily variability (p=.046) and lower rhythm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“… 9–13 Several studies using 24-hour accelerometer data have found that individuals with type 2 diabetes have impaired rest-activity rhythms, indexed by decreased overall rhythmicity and increased fragmentation. 14 15 A recent study 16 in older men (≥65 years) further observed that impaired rest-activity rhythm was not only associated with insulin resistance and type 2 diabetes at baseline but also associated with a higher risk of incident type 2 diabetes 3.5 years later, implicating that rest-activity rhythm may serve as a unique predictor of metabolic dysfunction.…”
Section: Introductionmentioning
confidence: 96%
“… 9–13 Several studies using 24-hour accelerometer data have found that individuals with type 2 diabetes have impaired rest-activity rhythms, indexed by decreased overall rhythmicity and increased fragmentation. 14 15 A recent study 16 in older men (≥65 years) further observed that impaired rest-activity rhythm was not only associated with insulin resistance and type 2 diabetes at baseline but also associated with a higher risk of incident type 2 diabetes 3.5 years later, implicating that rest-activity rhythm may serve as a unique predictor of metabolic dysfunction.…”
Section: Introductionmentioning
confidence: 96%
“…The levels of these biomarkers were reduced in patients with higher amplitudes, implying that higher RA was negatively correlated with cognitive decline, which is consistent with the findings of this study. In addition, previous studies have observed that lower RA is closely related to diseases such as abnormal glucose tolerance and diabetes ( 13 , 26 , 27 ). Compared with normoglycemic older adults, the elderly with diabetes were more likely to have MCI.…”
Section: Discussionmentioning
confidence: 94%
“…Although circadian rhythm alteration secondary to the presence of T2D has been studied [ 30 ], studies of human circadian rhythms have shown that under the standard 24 h daily cycle, the circadian pattern is not purely sinusoidal, but is modelled by a 12 h component (second harmonic), which has been related to the interaction between the homeostatic and circadian sleep regulatory components [ 31 ]. The presence of this 12 h rhythm is noticeable by a post-noon peak in wrist temperature rhythm or by a post-noon dip in activity.…”
Section: Discussionmentioning
confidence: 99%